2018
DOI: 10.1097/md.0000000000010988
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of abdominal body compositions on survival in advanced pancreatic cancer

Abstract: To investigate the clinical impact of body composition on outcomes in advanced pancreatic cancer (APC), we performed a retrospective analysis of patients diagnosed with APC between 2010 and 2016. The extent of visceral fat, subcutaneous fat, and skeletal muscle was measured using computed tomography (CT) images, together with visceral to subcutaneous adipose tissue area ratio (VSR) and skeletal muscle index (SMI). The effects of these body composition parameters on survival in APC were explored. In total 203 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
1
22
0
5
Order By: Relevance
“…A high VFR represents a high amount of intraabdominal fat tissue (VFA) in relation to the subcutaneous fat tissue (SFA). This finding of a prognostic impact of high VFR aligns with other studies conducted with pancreatic cancer patients [ 34 , 35 ] or lung cancer patients [ 9 ], where a high VFR turned out to be a predictor of poor prognosis. This prognostic impact seems to be consistent across several cancer entities.…”
Section: Discussionsupporting
confidence: 90%
“…A high VFR represents a high amount of intraabdominal fat tissue (VFA) in relation to the subcutaneous fat tissue (SFA). This finding of a prognostic impact of high VFR aligns with other studies conducted with pancreatic cancer patients [ 34 , 35 ] or lung cancer patients [ 9 ], where a high VFR turned out to be a predictor of poor prognosis. This prognostic impact seems to be consistent across several cancer entities.…”
Section: Discussionsupporting
confidence: 90%
“…Body fat primarily consists of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT), which are not only located in two distinct compartments, but also have different metabolic activities and impact on disease progression 7 . Meanwhile, the prognostic value of SAT and VAT remains a subject of debate in many types of cancer 3,4,6,8–12 …”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) scan has been used to measure visceral fat area (VFA) and subcutaneous fat area (SFA), and the ratio of VFA/SFA (VSR) as indicators of visceral obesity. In various solid malignancies, it has been suggested that visceral obesity is associated with worse outcomes [6-10]. However, to our knowledge, there is no study evaluating visceral obesity as a prognostic factor in lung cancer.…”
Section: Introductionmentioning
confidence: 99%